Comportamiento sexual de Triatoma gerstaeckeri Stal (Hemiptera: Reduviidae) - García Pérez, Jaime; Blanco Píñón, Alberto; Navarro Fernández, Eloísa (Instituto de Ecología, A.C., 1997)
T. gerstaeckeri does not exhibit a precopulatory courtship pattern during sexual encounters. Under laboratory conditions males lócate females through accidental contact followed by mounting and copulation. Fermales may copúlate as many as three times in one hour but each time with a different male. Mating duration may vary in length according to the number of males present, but it lasts on average 15 ± 5 min. During the first 3 min, 70% of males extend their proboscis and touch the female with it at an angle ranging from 45' to 90'. Males can copúlate twice as máximum in one hour. Sexual behavior consists in 7 steps. Females exhibit two different behaviors to avoid copulation: to flee or to struggle (if the male has already mounted the female). Males jerk rhythmically if they are mounted by an individual (male or female), It seems that thís behavior indicates to the mounting individual the sex and sexual receptivity of the mounted individual, It is discussed that sexual behavior of this bug is not steroetyped.